(NmEHANIZMY PROTIWOQZWENNOGO DEJSTWIQ MEDIATORNYH AMINOKISLOT I IH \NDOGENNYH METABOLITOW (B/s - d; (NtATEWOSQN(B, (NaLEKSEJ tEWANOWI^s ((NeREWAN (B:s (NaJASTAN(B,s, 1989)
(NrEZ@ME(B: (NANGL(B.s
(NbIBLIOGR(B.: (NS(B. 110-122s
Keywords: (NmEDICINAs; (NgASTRO\NTEROLOGIQs